ATIVIDADE FÍSICA EM PESSOAS COM MAIS DE 60 ANOS: C. D. PUERTO SAJONIA, ASSUNÇÃO (Fiep Bulletin - online, 2026)
This research on physical activity in adults over 60 years of age who attend the Puerto Sajonia Sports Club stems from an interest in understanding how movement and sports contribute to overall well-being at this stage of life. The study was based on the question: What physical activities do adults aged 60 and over engage in? The project aimed to identify the physical activities practiced by adults aged 60 and over. The methodology employed was a descriptive, quantitative, cross-sectional, and non-experimental study. A structured survey with closed-ended questions was used as the data collection technique, allowing for the precise collection and quantification of information. The study population consisted of 30 older adults who regularly attend the club. Relevant information was obtained, including: 93% stated that physical conditioning significantly contributes to improving their health, and 100% would recommend it to others. These findings suggest that physical activity and participation in events at the Puerto Sajonia Sports Club provide comprehensive benefits for adults aged 60 and over, improving their quality of life and promoting active aging. Therefore, the creation and implementation of physical activity programs, supported by both government and private institutions, is recommended to expand access to sports and recreational activities for this population group.
Keywords: Atividade física; Idosos; Acima de 60 anos; Bem-estar integral; Clube Desportivo Puerto Sajonia